Non-Penal Policy in Combating Love Scamming - Mutmainah Nur Qoiri; La Ode Muhammad Ichsan (Semarang State University Undergraduate Law and Society Review, 2025)
One of today’s contemporary forms of crime, love scamming, inflicts huge financial and psychological losses on victims. This crime is increasingly complicated because it involves emotional relationships that are difficult for victims to recognize as a form of fraud. This research aims to examine and implement non-punitive policies as a prevention strategy against love scamming. The method used is a normative-empirical approach, which combines the study of applicable law and direct observation of existing social phenomena. With a socio-legal approach, this research analyzes the social response to love scamming. The results show that love scamming is influenced by structural factors such as economic inequality and weak emotional self. The research shows that in carrying out their actions, the perpetrators deceive the victims and take advantage of the emotional weakness and vulnerability of the victims. Non-penal efforts considered strategic for victims include increasing self-awareness in social media interactions. Meanwhile, to minimize crime, stakeholders can provide maximum limits on registering accounts in the application and prohibit creating anonymous accounts without a clear identity. This research not only contributes to prevention efforts in general for social media account users but also specifically for vulnerable groups such as women who are easily manipulated emotionally, and children and parents who are struggling with the use of technology and are at higher risk of becoming victims of love scamming.